Development and mathematical modelling of a dual-rotor machine for wind turbine power generation system - Yanan Li; Jianhui Cui; Hongna Li; Bin Zhao (Scientific Reports)
Abstract Insufficient power grid support for wind turbines has become evident as wind energy use rises, particularly with bigger turbines. This paper introduces a modeling approach for a dual-rotor machine. Furthermore, it proposes a mechanism to integrate the gearbox and synchronous generator with the dual-rotor assembly to serve as a front-end speed control system. The synchronous generator at the end of the drive chain removes the need for a converter to connect electricity to the grid, making dual-rotor wind power production grid-compatible. Given the unique construction of the dual-rotor machine in this proposed system, the conventional mathematical model is no longer suitable for representing such machinery. To solve this problem, a mathematical model is created for the inner rotor of these machines utilizing a “rotating relative coordinate system” and a “relative stationary coordinate system” that stays stationary with the inner rotor while spinning for space. The mathematical model for the dual-rotor system is built on this basis. Final MATLAB simulations prove the unique mathematical model’s viability and the two-rotor wind turbine system’s power production efficiency. This study underscores the potential of this approach in advancing wind energy technology.